Measurement of Noise within Passenger Trains on a Costal Railway Line - Pahalavithana, N.S.; Sonnadara, D.U.J. (My University, 2009)
The noise levels within passenger trains operating on a coastal railway line is presented. It was found that the engine noise is the main source of traction noise. Its contribution to the overall noise level within the passenger compartments was analyzed, and, the effect of engine noise on the passengers has been discussed. Noise enhancement due to external objects in close proximity to the railway line was carried out in order to assess the total noise exposure of the passengers in a train traveling on the costal railway line. In general passengers are exposed to average noise levels around 75 dB which can reach 85 dB in passenger compartments close to the engine of the train. A simple noise prediction model is proposed which was successful in predicting the average noise level within passenger compartments in trains running between two adjacent stations along the selected coastal railway line.
Keywords: Noise within Passenger; Trains; Costal Railway Line